The Effectiveness of the Malaysian Guidelines for Pre-operative COVID-19 Screening in ORL Patients Undergoing Elective Surgery - Nor Azirah Salahuddin; Siti Asmat Md Arepen; ShahrulHitam; Eyzawiah Hassan (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]